Pengawasan Pelaksanaan Sistem Outsourcing yang Berbasis Pada Hak Asasi Manusia - Solechan Solechan (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2019)
This study aims to find out, First, knowing the conditions of labor inspection; Second, knowing the efforts to optimize the supervision of outsourcing systems oriented to human rights. This method of writing scientific papers uses the writing of juridical-normative law, with a statutory approach. The results of writing indicate that: First, enforcement of labor law is not optimal. It is known from the existence of problems that occur, among others, the absence of social security, very low wages and the placement of outsourced workers who are not in accordance with the laws and regulations make outsourcing workers lose their basic rights. Second, efforts to optimize the supervision of outsourcing systems oriented to human rights can be done through the enforcement of integrated labor law. Supervision of the outsourcing system must emphasize protection (to protect), fulfillment (to fulfill), and respect to be more optimal. Therefore, concrete steps are needed in the enforcement of labor law. One of them is the establishment of a complaint center specifically centered at the Ministry of Manpower and integrated with the provincial level Manpower and Transmigration Office. This call center serves complaints about violations and is expected to improve the performance of labor inspectors. Keywords: Supervision, Outsourcing System, Human Rights Abstrak Penelitian ini bertujuan untuk mengetahui, Pertama, mengetahui kondisi pengawasan bidang ketenagakerjaan; Kedua, mengetahui upaya optimalisasi pengawasan sistem outsourcing yang berorientasi pada Hak Asasi Manusia. Metode penulisan karya tulis ilmiah ini menggunakan penulisan hukum yuridis-normatif, dengan pendekatan statutory approach. Hasil penulisan menujukan bahwa: Pertama, penegakan hukum ketenagakerjaan belum optimal. Hal tersebut diketahui dari masih adanya persoalan-persoalan yang terjadi antara lain tidak adanya jaminan sosial, upah yang sangat rendah dan penempatan tenaga kerja outsourcing yang tidak sesuai dengan peraturan perundang-undangan menjadikan tenaga kerja outsourcing kehilangan hak-hak dasarnya. Kedua, upaya optimalisasi pengawasan sistem outsourcing yang berorientasi pada Hak Asasi Manusia dapat dilakukan melalui penegakan hukum ketenagakerjaan terpadu. Pengawasan sistem outsourcing harus menekankan pada perlindungan (to protect), pemenuhan (to fulfill), dan penghormatan (to respect) agar lebih optimal. Oleh karena itu, diperlukan langkah konkret dalam penegakan hukum ketenagakerjaan. Salah satunya dengan pembentukan call center khusus pengaduan yang terpusat di Kementerian Ketenagakerjaan dan terintegrasi dengan Dinas Tenaga Kerja dan Transmigrasi tingkat provinsi. Call center ini melayani pengaduan atas terjadinya pelanggaran dan diharapkan dapat meningkatkan kinerja pengawas ketenagakerjaan. Kata Kunci: Pengawasan, Sistem Outsourcing, Hak Asasi Manusia